Prevalence of Diabetes, Prediabetes, and Associated Factors in an Adult Chinese Population: Baseline of a Prediabetes Cohort Study - Xinjie Yu; Fang Duan; Da Lin; Hai Li; Jian Zhang; Qiuyu Wang; Xianglong Wang; Qian Zhao; Jiayu Deng; Guangwei Song; Qingqing Ji; Haihua Zheng; et al. (International Journal of Endocrinology)
Purpose. To report baseline information of a prediabetes mellitus (PDM) cohort with the aim of exploring related factors for the progression of PDM and its complications. Methods. This study is an exploratory and cross-sectional analysis of the baseline data from a cohort study. Residents aged 18 to 70 years from Houtang Village, Nanyue Town, Yueqing City, Zhejiang Province, China, were invited to participate between October 1, 2018 and July 1, 2019. Blood samples were collected for analysis, and questionnaire interviews were conducted to assess behavioral characteristics. The study participants were divided into DM, PDM, and normal groups for comparisons based on their blood work, and multiple multinomial logistic regression analyses were used to assess the risk factors for DM and PDM. Results. Data from 406 participants were used in the baseline analysis, with a mean age of 51.2 ± 11.0 years and 160 (33.0%) males. The number of participants in the DM, PDM, and normal group was 58 (14.3%), 166 (40.9%), and 182 (44.8%), respectively. The prevalence of DM was 14.3%, and the prevalence of PDM was 40.9%. The regression analysis showed that older age (relative risk ratio (RRR) = 1.06; 95% CI, 1.01–1.11, P=0.018), higher systolic blood pressure (RRR = 1.04; 95% CI, 1.004–1.08, P=0.030), higher BMI (RRR = 1.20; 95% CI, 1.06–3.06, P=0.004), higher TG (RRR = 1.80; 95% CI, 1.06–3.06, P=0.029), and higher WBC count (RRR = 1.32; 95% CI, 1.07–1.64, P=0.010) were significantly associated with a higher risk of DM. Meanwhile, higher systolic blood pressure (RRR = 1.03; 95% CI, 1.004–1.06, P=0.025) was the only factor significantly associated with a higher risk of PDM. Conclusion. The prevalence of DM and PDM is relatively high in this wealthy East China village population. Many modifiable risk factors exist for DM and PDM, which will be closely monitored during our longitudinal observation.